Multi Objective Flexible Employee Scheduling for Pharmaceutical Industries Using Hybrid Genetic Algorithm (Journal of Pharmaceutical Negative Results, 2022)
In this paper a hybrid genetic algorithmis used to study the employee scheduling problem in pharmaceutical industries. Scheduling is done based on the aspects of both management and employees. The management aspect is to reduce the total cost of the employee by minimizing the makes span. The employee aspects are a preferred number of shifts, shift types, days off, etc. In this scheduling an extra care is taken in not to assign a night shift on the day beforethe day off, because once a night shift assigned to the employee almost present in the next morning. A mathematical model is formed based on flexible working of the employees. In this model, 6 hour shifts isallotted to the employees, which reduces the total cost by 10.135% and the makes span by 4.145% compared to the other models.